Presidents, Assembly Dissolution, and the Electoral Performance of Prime Ministers. (May 2018) - Schleiter, Petra; Morgan-Jones, Edward
Many European presidents have extensive constitutional powers to affect the timing of early parliamentary elections, which enables them to influence when incumbent governments must face the electorate. This article examines whether presidents use their assembly dissolution powers for partisan benefit. To date, presidential activism in the electoral arena of parliamentary and semipresidential democracies remains poorly understood. We hypothesize that presidents use their powers to influence election calling for the advantage of their political allies in government. To test this argument, we use data on 190 elections in 18 European democracies. Our results suggest that presidents with significant dissolution powers are able to shape the electoral success of incumbents. Prime ministers whose governments are allied to such presidents realize a vote and seat share bonus of around 5%. These findings have implications for our understanding of presidential activism, strategic parliamentary dissolution, and electoral accountability.